Role of Teacher in Enhancing Quality Education of Secondary Level Public School of Nepal - Dahal, Tanka Prasad; Gupta, Pooja; Mishra, Chandreshwor (Nepal Journal of Multidisciplinary Research, 2019)
Teachers are the guardians of civilization; they are the role model for the students. So, the role of teacher is very important to enhance the quality education and increase the performance of students. The main objective of this study was to identify the role of teacher in enhancing the quality education. The study was conducted in Kathmandu, Dhanusa, Dolakha and Ramechhap district among the 388 stakeholders of education. Mixed method was used to collect the data. The result revels that there was significant different in the current level and expected level in role of teachers. The mean value of expected level was higher than the current level of role of teachers in enhancing the quality education so it can be concluded that there is need of improvement in the role of teachers. The concerned authority of schools should provide the opportunity to teachers to participate in the advance level of training program to enhance their teaching and learning capacity which ultimately can contribute in the quality education of school.